The Effect of Problem-Based Learning Model on Student's Mathematic Connection Ability in Mathematics Learning in SMP N.1 Rantau Utara - Dessy Syahfitri; Eva Julyanti (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine students' mathematical connection abilities in the application of problem-based learning models and to determine the effect of student learning using problem-based learning models at SMP Negeri 1 Rantau Utara. The research method used is quasi-experimental research, The population in this study were all students of class VIII SMP Negeri 1 Rantau Utara for the Academic Year 2021/2022 as many as 288 people, then from 8 classes, two classes were selected as samples, namely class VIII-2 which consisted of 36 students who were taught by problem-based learning model, class VIII-5 consisted of 36 students who were taught by conventional learning model.The analytical technique used is descriptive analysis to describe student activities, teacher's ability to manage learning, and student response processes. The results of the analysis of the Gain data for the problem-based learning model class with the conventional model class using the t-test obtained the value of tcount= 8,54 from the distribution list t for  = 0,05, and dk = n1 – n2 – 2 or dk = 70 obtained ttable= 1,959. By comparing between ttable and tcount obtained tcount > ttable then Ha is accepted. Thus, the results of this study can be stated that there is an effect of problem-based learning models on increasing students' mathematical connection abilities.